The characterisation of Abelson Helper Integration Site-1 in skeletal muscle and its links to the metabolic syndrome - Prior, Matthew J. (2009)
The human Abelson helper integration site-1 (AHI1) gene is associated with both neurological and haematological disorders; however, it is also located in a chromosomal region linked to metabolic syndrome phenotypes and was identified as a type 2 diabetes susceptibility gene from a genome-wide association study. To further define a possible role in type 2 diabetes development, AHI1 mRNA expression levels were investigated in a range of tissues and found to be highly expressed in skeletal muscle as well as displaying elevated levels in brain regions and gonad tissues. Further analysis in a rodent, polygenic animal model of obesity and type 2 diabetes identified increased Ahi-1 mRNA levels in red gastrocnemius muscle from fasted impaired glucose tolerant and diabetic rodents compared with normal animals (p<0.002). Moreover, elevated gene expression levels were confirmed in skeletal muscle from fasted obese and type 2 diabetic human subjects (p≤0.02). RNAi-mediated suppression of Ahi-1 resulted in increased glucose transport in rat L6 myotubes in both the basal and insulin-stimulated states (p<0.01). Finally, SNP association studies identified two novel AHI1 genetic variants linked with fasting blood glucose levels in Mexican American subjects (p<0.037). These findings indicate a novel role for AHI1 in skeletal muscle and identify additional genetic links with metabolic syndrome phenotypes suggesting an involvement of AHI1 in the maintenance of glucose homeostasis and type 2 diabetes progression.